Urological, vascular, and infectious implications of kidney transplant: a single-center experience - Juan G. Prada; Sofía Manjarrés-Sierra; Isabella Lince-Rivera; Carolina Martínez-Pinedo; Carolina Martínez-Pinedo; Germán Patiño; Hugo E. López (Urología Colombiana)
Introduction: Kidney transplant has improved in the last decades due to new technologies and surgical techniques. However, there are still multiple complications associated with this procedure, which can affect the function and viability of the kidney graft. Our aim was to describe the incidence of urological, vascular, and infectious complications in the 1st month after the procedure. Methods: A cross-sectional and retrospective study was carried out. Records of all patients who underwent kidney transplant from 2007 to 2017 were reviewed and data of demographic and surgical variables as well as information of vascular, urological, and infectious complications during the 1st post-operative month were registered and analyzed. Results: A total of 243 patients that required kidney transplant were assessed. The most common chronic kidney disease etiologies were: idiopathic (25.5%), glomerulopathies (24.7%), and hypertension (23.5%). Seventy patients (28.8%) presented a complication, of which 31 were urological, 27 were infectious, and 12 were vascular. In each category, the most frequent complications were the perirenal hematoma, the urinary tract infection, and renal artery stenosis, respectively. Conclusions: The prevalence of complications found in our center is similar to that reported in the literature and it is significant. It is important for medical personnel to be aware of this data to have a high level of suspicion and make an active search, as an early diagnosis and treatment of these pathologies are crucial to avoid graft loss.